2001
DOI: 10.1177/089686080102100406
|View full text |Cite
|
Sign up to set email alerts
|

Trends in CAPD Technique Failure: Canada, 1981–1997

Abstract: Objective Although important enhancements to continuous ambulatory peritoneal dialysis (CAPD) have occurred since its inception, few studies have explicitly evaluated trends over time in CAPD technique failure rates. To assist in quantifying the net benefit of improvements to CAPD for patient outcomes, we examined trends in technique failure rates among Canadian CAPD patients. Patients Patients initiating renal replacement therapy on CAPD ( n = 7110) between 1981 and 1997. Main Outcome Measures Technique failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…The 2-year technique survival for our study patients was 63%. Peritonitis was strongly associated with technique failure in our patients, a finding that has been confirmed by others (23)(24)(25). The low peritonitis rates seen in our study help to explain the high technique survival we observed.…”
Section: Discussionsupporting
confidence: 90%
“…The 2-year technique survival for our study patients was 63%. Peritonitis was strongly associated with technique failure in our patients, a finding that has been confirmed by others (23)(24)(25). The low peritonitis rates seen in our study help to explain the high technique survival we observed.…”
Section: Discussionsupporting
confidence: 90%
“…Peritonitis not only is the leading cause of technique failure but also contributes to mortality. [3][4][5][6][7][8][9][10][11][12][13][14][15] In a single center study of a PD cohort of 516 adults, the rate of death from all infections or sepsis was 30 per 1000 dialysis years at risk. 8 Ninety-two percent of these deaths due to infection were related to peritonitis.…”
mentioning
confidence: 99%
“…1 In other parts of the world, infection also continues to be the second most common cause of death in PD patients. 9 Peritonitis also continues to be the leading cause of technique failure, [9][10][11] and for years has been a leading cause of hospitalization. 12 Therefore, to improve outcomes in peritoneal dialysis patients, attention must be focused on preventing peritonitis.…”
mentioning
confidence: 99%
“…Non-infectious complications of CAPD are increasing in relative importance due to success in decreasing the rate of peritonitis. Catheter related problems are the major causes of technique failure and account for approximately 20% of change to HD [2,3].…”
Section: Introductionmentioning
confidence: 99%